Trends in Population-based Cancer Survival in Slovenia - Zadnik, Vesna (Radiol Oncol, 2021)
BACKGROUND: The aim of our study was to describe the survival of Slovenian cancer patients diagnosed in the last twenty years. An insight is given into the improvement made in different cancer types, population groups and prognostic factors. MATERIALS AND METHODS: The principal data source was the population-based Slovenian Cancer Registry. The survival analysis included patients diagnosed with cancer in twenty years period from 1997 to 2016, which has been divided into four consecutive five-year periods. In addition, the analysis was stratified by cancer type, gender, age and stage. The survival was estimated using net survival calculated by the Pohar-Perme method and the complete approach has been applied. RESULTS: The survival of Slovenian cancer patients has been increasing over time. During the 20 years observed, five-year net survival increased by 11 percentage points. Significantly higher growth was observed in men. Age and stage at diagnosis are still crucial for the survival of cancer patients. Five-year net survival is lowest in those over 75 years of age at diagnosis but has also improved by seven percentage points over the past 20 years. The five-year net survival of patients in the localized stage increased by ten percentage points over the 20 years under observation. Survival of patients in the distant stage has not been improving. In both sexes, survival for melanoma, colorectal and lung cancers have increased significantly over the last 20 years. Progress has also been made in the two most common gender specific cancers: breast cancer in women and prostate cancer in men. Still, the significant progress in prostate cancer is probably mostly due to lead-time bias as during the study period, Slovenia used indiscriminate PSA testing, which probably artificially prolonged survival. CONCLUSIONS: The survival of Slovenian cancer patients has been increasing over time, which gives us a basis and an incentive for future improvements. To monitor the effectiveness of managing the cancer epidemic, the cancer burden needs to be monitored also in the future, using quality data and scientifically justified methodological approaches. In this process a well organised population-based cancer registries should play a key role.